Comparison of quality of sausages from chicken and rabbit meat - KUMAR, SUSHIL; MENDIRATTA, S K; KESHRI, R C (The Indian Journal of Animal Sciences, 2013)
Studies were, conducted to compare quality parameters of sausages prepared from chicken and rabbit meat in proportions of 100:0, 75:25, 50:50, 25:75 and 0:100 respectively. Results indicated significantly (P<0.01) higher emulsion stability and cooking yield in ’all-rabbit’ than in ’all-chicken’ sausages. There was no significant difference in shear force values, moisture and ash contents among sausages of different formulations. All-rabbit sausages were significantly (P<0.01 ) higher in protein but lower in fat content than ’all-chicken’ sausages. No significant difference in microbial counts among the sausages was observed. Organoleptic scores indicated nonsignificant differences for appearance. colour. aroma. texture and juiciness. However, sausages containing 50:50 chicken and rabbit meat scored significantly (P<0.05) higher for flavour and overall palatability than all-rabbit meat sausages. Study indicated that rabbit meat can be effectively incorporated in chicken sausages without affecting the overall quality.